Staphylococcus aureus Lpl Lipoproteins Delay G2/M Phase Transition in HeLa Cells - Nguyen, Minh-Thu; Deplanche, Martine; Nega, Mulugeta; Le Loir, Yves; Peisl, Loulou; Götz, Friedrich; Berkova, Nadia (Frontiers in Cellular and Infection Microbiology, 2016)
The cell cycle is an ordered set of events, leading to cell growth and division into two daughter cells. The eukaryotic cell cycle consists of interphase (G₁, S, and G₂ phases), followed by the mitotic phase and G₀ phase. Many bacterial pathogens secrete cyclomodulins that interfere with the host cell cycle. In Staphylococcus aureus four cyclomodulins have been described so far that all represent toxins and are secreted into the culture supernatant. Here we show that the membrane-anchored lipoprotein-like proteins (Lpl), encoded on a genomic island called νSaα, interact with the cell cycle of HeLa cells. By comparing wild type and lpl deletion mutant it turned out that the lpl cluster is causative for the G2/M phase transition delay and also contributes to increased invasion frequency. The lipoprotein Lpl1, a representative of the lpl cluster, also caused G2/M phase transition delay. Interestingly, the lipid modification, which is essential for TLR2 signaling and activation of the immune system, is not necessary for cyclomodulin activity. Unlike the other staphylococcal cyclomodulins Lpl1 shows no cytotoxicity even at high concentrations. As all Lpl proteins are highly conserved there might be a common function that is accentuated by their multiplicity in a tandem gene cluster. The cell surface localized Lpls' suggests a correlation between G2/M phase transition delay and host cell invasion.